Monarchs of the Nile - Dodson, Aidan, 1962- (American University in Cairo Press, 2000)
"This book presents a concise account of the lives and times of some of the more significant occupants of the Egyptian throne, from the unification of the country around 3000 B.C. down to the extinction of native rule just under three millennia later. Some, such as Tuthmosis III, had a major impact on their time, and were remembered by their own people until the very civilization collapsed. Others, such as Tutankhamun, were soon forgotten by the Egyptians themselves, only to burst into popular culture thousands of years after their deaths, as a result of the labors of modern archeologists. Still more remain unknown outside the small circle of professional archeologists, but led lives that call out for wider dissemination. This book sets out to provide a mix of all three categories, in an attempt to present a balanced view of Egyptian kings and their range of achievements."--Jacket